VISI PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Rita Sukaesih; Muhammad Saleh Suhaidy; Muhammad Al Mighwar; Ujang Nurjaman (Fakultas Agama Islam Universitas Wiralodra, 2022)
This study aims to describe and analyze the what, why, and how of the vision of education based on religion, philosophy, psychology, and sociology. The results of this study are that the vision of education is the ideal and realistic ideals of human empowerment to be realized in the future which is: (1) based on religion means that it is inspired by the belief and superpower of God's control because it is related to universal values, by examining His verses, purify oneself, study the Qur'an and its meaning in its entirety, and develop knowledge; (2) based on philosophy means that which is inspired by knowledge and reality as well as fundamental existence because it is related to the existence of human thought, which is carried out by means of the study of intelligence instruments, experiments, and the environment; (3) based on psychology means that are inspired by cognitive and behavioral sciences because they are related to the existence of human consciousness, by means of analysis studies of ID, ego, and superego; and (4) based on sociology means that is inspired by social science because it is related to the existence of reciprocal reactions to people's behavior, by means of the exchange of social potentials